Pengaruh Kompetensi Dan Disiplin Kerja Terhadap Kinerja Pegawai Balai Diklat Keagamaan Kota Palembang - Yudha Oktapratama; Aliasan Aliasan; Hasril Atieq Pohan (Social Science and Contemporary Issues Journal, 2023)
The thesis entitled "The Influence of Competence, Work Discipline on Employee Performance at the Palembang City Religious Education and Training Center". The problems are first, does work discipline have a partial effect on employee performance?, Second, does competence have a partial effect on employee performance?. Third, do competence and work discipline influence simultaneously on the performance of employees of the Palembang City Religious Education and Training Center? This type of research used is quantitative research. Data collection techniques include observation, questionnaires and documentation with data analysis techniques including validity, reliability, normality, multicollinearity, heterocadesity, multiple linear and hypothesis testing. Research results 1) There is a positive and significant influence that competence has a partial effect on employee performance at the City Religious Education and Training Center, namely the tcount value is greater than ttable (4.577 > 0.68024) and the significance value of t variable X1 (sig t) is sig t (0.006) < α(0.05). 2) There is a positive and significant effect of work discipline partially on employee performance at the Palembang City Religious Education and Training Center with a variable value X2 = 0.008<0.05. The value of 0.317 is an increase from std. error r = 0.113 so that it can be ascertained that there is an influence between variable X2 (work discipline) on variable y (employee performance). 3) F-count value of 10,831; means that the F-count value (10,831) > ftable (2.83), while the sig f value is (0.000) <α (0.05), the decision is to reject Ho and accept Ha, then there is a positive and significant influence on competence, work discipline simultaneously on the Performance of Employees of the Palembang City Religious Education and Training Center.